How are adolescents engaged in obesity and chronic disease prevention policy and guideline development? A scoping review - Mariam Mandoh; Julie Redfern; Seema Mihrshahi; Hoi Lun Cheng; Philayrath Phongsavan; Stephanie R. Partridge (BMC, 2023)
Abstract Background Adolescent consumer engagement is widely accepted, with global calls to meaningfully involve adolescents for effective and tailored policy and guideline development. However, it is still unclear if and how adolescents are engaged. The aim of this review was to determine if and how adolescents meaningfully participate in policy and guideline development for obesity and chronic disease prevention. Methods A scoping review was conducted guided by the Arksey and O'Malley six stage framework. Official government websites for Australia, Canada, United Kingdom, and United States including intergovernmental organizations (World Health Organisation and United Nations) were examined. Universal databases Tripdatabase and Google advanced search were also searched. Current and published international and national obesity or chronic disease prevention policies, guidelines, strategies, or frameworks that engaged adolescents aged 10-24 years in meaningful decision-making during the development process were included. The Lansdown-UNICEF conceptual framework was used to define mode of participation. Results Nine policies and guidelines (n = 5 national, n = 4 international) engaged adolescents in a meaningful capacity, all focused on improving 'health and well-being'. Demographic characteristics were poorly reported, still most ensured representation from disadvantaged groups. Adolescents were primarily engaged in consultative modes (n = 6), via focus groups and consultation exercises. Predominantly in formative phases e.g., scoping the topic or identifying needs (n = 8) and to a lesser extent in the final stage of policy and guideline development e.g., implementation or dissemination (n = 4). No policy or guideline engaged adolescents in all stages of the policy and guideline development process. Conclusion Overall, adolescent engagement in obesity and chronic disease prevention policy and guideline development is consultative and rarely extends throughout the entire development and implementation process.